2004
DOI: 10.1007/s00228-004-0735-2
|View full text |Cite
|
Sign up to set email alerts
|

Early antibiotic treatment of pseudomonas aeruginosa colonisation in cystic fibrosis: a critical review of the literature

Abstract: Evidence was found that antibiotic treatment can reduce the rate of positive cultures and of anti-PA antibody titres in asymptomatic CF patients with newly isolated PA. Different therapeutic options have not been directly compared: a multi-centre comparative study needs to be carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…Another pitfall of P. aeruginosa susceptibility testing in CF patients is the ever-increasing use of aerosolized agents, especially tobramycin and colistin [3]. Susceptibility testing is based on serum-achievable levels of the antimicrobial of interest.…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
See 2 more Smart Citations
“…Another pitfall of P. aeruginosa susceptibility testing in CF patients is the ever-increasing use of aerosolized agents, especially tobramycin and colistin [3]. Susceptibility testing is based on serum-achievable levels of the antimicrobial of interest.…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
“…Clearly, it can provide little guidance in CF patients infected chronically with P. aeruginosa for the reasons already discussed. However, it may offer guidance in patients in the early stages of P. aeruginosa infection in whom eradication using aerosolized antimicrobials, either alone or in combination with oral fluoroquinolones [3], is being attempted. In the early stages of CF disease, the planktonic mode of growth predominates and it is also less likely that the organisms are growing under anaerobic conditions [2].…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
See 1 more Smart Citation
“…Tobramycin is approved antibiotic in the United States and highly recommended for patients with CF to delay colonization of P. aeruginosa in the lungs (237). Six different independent studies showed significant improvement of lung functions in patients with moderate to severe CF and decreased chronic P. aeruginosa count and weight gain following tobramycin treatment compared to placebo or standard treatment (174,(238)(239)(240)(241)(242). Tobramycin delayed biofilm formation of P. aeruginosa as well as disruption of already formed biofilms thereby limits the growth of P. aeruginosa (243).…”
Section: Current Therapeutic Optionsmentioning
confidence: 99%
“…Patients with CF are treated with antibiotics to prevent and eradicate respiratory infections (241). Aminoglycoside antibiotics such as tobramycin, gentamicin has been shown to restore expression of full-length functional CFTR and significant increase of cAMP-activated chloride channel (180,263).…”
Section: Macrophages: the Missing Link In Cf Inflammation?mentioning
confidence: 99%